Exploring the Relationship between Ownership Structure and Financial Performance: An Empirical Analysis of Indonesian Companies - Setiawan, Yan Christianto (E-Jurnal Akuntansi; Vol 34 No 5 (2024)DO - 10.24843/EJA.2024.v34.i05.p02, 2024)
Ownership structure is one of the factors that influence management's decision-making, which in turn impacts the company's financial performance. This study aims to obtain empirical evidence regarding the effect of various types of ownership—including institutional, government, family, managerial, and foreign ownership—on financial performance in non-financial sector companies. The population in this study consists of all business entities listed on the IDX from 2018 to 2021. The sample size used in this study is 1,536 company-years, derived from 384 companies out of a total population of 2,781 on the IDX over four years. A purposive sampling technique was employed for selecting the sample. Researchers utilized a fixed effect model on the panel data structure for hypothesis testing analysis. The results showed that the presence of government, family, and foreign ownership improves the company's financial performance. Therefore, investors can consider ownership structure when making investment decisions. Keywords: Corporate governance; firm performance; ownership structure.